What is the Impact of the Implementation of Local Content of Komering Culture for Students and Teachers in East OKU? - Edi Riyanto; Cipto Budy Handoyo; Arif Rohman (Smart Society, 2025)
Komering's local cultural content has an important role in preserving local wisdom and instilling moral and social values in the younger generation. This study aims to analyze the impact of the local content of komering culture on students and teachers. The method used was quantitative descriptive with closed questionnaire instruments and suggestions from students and teachers. The study respondents consisted of 88 students and 31 teachers at the elementary and junior high school levels in OKU Timur district. The results of the study show that planning, implementation, assessment, material suitability, supporting facilities and environment and komering regional songs have a high positive impact on students and teachers. The percentage of students and teachers exceeded 70% in each aspect. Even so, the results of the analysis show that students and teachers have not used the language of komering to the maximum in learning, so they find it difficult when singing komering songs. This research contributes to teachers, students and local governments in developing local content materials of Komering culture. The next research recommendation is to analyze the ability of komering language both at the elementary, secondary and university levels